Mucosal IgA increase in rats by continuous CLA feeding during suckling and early infancy (2008)
The aim of this work was to establish the effect of the cis9,trans11 conjugated linoleic acid (CLA) isomer on mucosal immunity during early life in rats, a period when mucosal immunoglobulin production is poorly developed, as is also the case in humans. CLA supplementation was performed during three life periods: gestation, suckling, and early infancy. The immune status of supplemented animals was evaluated at two time points: at the end of the suckling period (21-day-old rats) and 1 week after weaning (28-day-old rats). Secretory IgA was quantified in intestinal washes from 28-day-old rats by ELISA technique. IgA, TGF?, and PPAR? mRNA expression was measured in small intestine and colon by real time PCR, using Taqman® specific probes and primers. IgA mucosal production was enhanced in animals supplemented with CLA during suckling and early infancy: in 28-day-old rats, IgA mRNA expression was increased in small intestine and colon by approximately 6- and 4-fold, respectively, and intestinal IgA protein by ?2-fold. TGF? gene expression was independent of age and type of tissue considered, and was not modified by dietary CLA. Gene expression of PPAR?, a possible mediator of CLA's effects was also upregulated in animals receiving CLA during early life. In conclusion, dietary supplementation with CLA during suckling and extended to early infancy enhances development of the intestinal immune response in rats.